Recuperación de oro por gravimetría de mineral proveniente de la Herradura - Chinapintza - Espinoza Maldonado, Jessica Karina (2014)
This research sponsored by the Department of Mines and Geology and Civil Engineering at the Technical University of Loja, is aimed at the application of gravimetric methods for gold recovery with regard to mine Chinapintza district. The work was developed from the tour and sampling at the Herradura mine district - where Chinapintza vein material and proper laboratory tests and analysis took office. By applying metallurgical tests and shaking table Knelson separately and combined, allow us to determine the percent recovery of gold. The research project contributes to information about applying the mining metallurgical testing, taking into account that these are not aggressive to the environment and to apply their results are feasible and favorable.